The role of internal auditors in fraud prevention: A systematic literature review (SLR) - Irianti, Lingga Resvita; Nuswantara, Dian Anita; Pujiono, Pujiono (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2025)
This study aims to systematically examine the role of internal auditors in fraud prevention using a Systematic Literature Review (SLR) approach. Fraud poses a serious threat to organizational sustainability, making the role of internal auditors crucial in detecting and preventing fraudulent activities. This study reviewed five relevant articles published between 2020 and 2024, focusing on the contribution of internal auditors to the effectiveness of internal controls, early detection of anomalies, development of whistleblowing systems, and anti-fraud education. The findings reveal that internal auditors play a strategic role in fostering an organizational culture of integrity and transparency and narrowing the opportunities for fraud. However, the effectiveness of this role is influenced by factors such as auditor independence, management support, professional competence, and adequate resource allocation. Key challenges identified include managerial pressure and resource limitations. This study recommends collective organizational support to strengthen the internal audit function and create a sustainable fraud prevention system. The results are expected to provide theoretical and practical insights for enhancing the role of internal auditors in safeguarding organizational integrity